Hepatitis C and hepatitis B virus infections in the etiopathogenesis of pemphigus - Gulsen Tukenmez Demirci; Ikbal Esen Aydingoz; Ayse Tulin Mansur; Guldehan Atis; Ilknur Kivanc Altunay (Sociedade Brasileira de Dermatologia, 2014)
BACKGROUND:Previous studies have shown that some viral infections may be triggers for autoimmune diseases. The role of viral infections in the etiopathogenesis of pemphigus has also been investigated.OBJECTIVES:To investigate the relationship between pemphigus and the hepatitis B and C virus infections.METHODS:This retrospective study included 62 patients with pemphigus and 50 healthy controls of matching ages and genders. The control group included relatives who accompanied the orthopedic patients to the hospital but had no history of systemic and/or autoimmune diseases.RESULTS:The group of patients with pemphigus was composed of 43 (69.3%) females and 19 (29.7%) males, and the mean age was 48.08 ± 15.38. The hepatitis C virus antibody was negative in all of the patients. Hepatitis B surface antigen (HBsAg), hepatitis B surface antibody (HBsAb), or both, were studied in 44 of the 62 patients. Two (4.3%) of these patients were positive for HBsAg and found to have HBV infection. Fourteen of them were HBsAb positive. Two (4%) of the 50 control subjects showed hepatitis C virus antibody positivity, while only 1 (2%) patient with pemphigus displayed HBsAg positivity. There was no statistically significant difference between the two groups for hepatitis B and C virus infections.CONCLUSIONS:This study does not support an association between pemphigus and hepatitis B and/or C virus infections.